THE EFFECTIVENESS OF PSYCHOEDUCATION IN INCREASING KNOWLEDGE ABOUT BULLYING AMONG EARLY ADOLESCENTS AT SMPN 63 SURABAYA THROUGH THE SANG SURYA PSYCHOLOGICAL SERVICE UNIT (UPP) - Saputra, Dasril; Puspitaningrum, Noer Suci Endah (Universitas Tanjungpura, 2025)
This study aims to determine the effectiveness of psychoeducation in increasing knowledge about bullying in early adolescents at SMPN 63 Surabaya through the Sang Surya Psychological Service Unit (UPP). The background of this study is based on the rampant cases of bullying among adolescents, which indicates that students still have a low understanding of the forms, impacts, and ways to prevent bullying. The study used a quantitative method with a one-group pretest-posttest design, where participants were given a pretest before the psychoeducational intervention and a posttest afterward to measure the increase in knowledge. The results showed a significant increase in students' knowledge about bullying after participating in the psychoeducational program, which included material on the types of bullying, psychological impacts, and prevention and handling strategies. Thus, psychoeducation implemented through the UPP Sang Surya has proven effective in increasing the knowledge and awareness of early adolescents about bullying in the school environment.